Hierarchical Composite Materials Materials, Manufacturing, Engineering - Abdulrahman, Kamardeen O.; Abed, Alaaeddin M. H.; Bayode, Abiodun; Bhowmick, Shubhankar; Davim, J. Paulo; Dey, Sudip; Duy Hien, Ta; Faris M, AL-Oqla; Karsh, Pradeep Kumar; Kumar Gaba, Vivek; Kumar Singh, Akant; Kumar Singh, Prashant; et al. (Advanced Composites ;, 2018)
Hierarchical Composite Materials provides an in-depth analysis of a class of advanced composites that have properties that are anisotropic due to structural organization at different length scales. Chapters address how ordering occurs from the atomic-scale up to the microstructure and how control of these factors leads to the final materials' properties. Manufacturing procedures, properties, and applications of different functionally graded materials are discussed in detail. This book is ideal for materials scientists, mechanical engineers, chemists and physicists.